Learning Model Development Locomotor For Student Elementary School - Ramadhani, Tivany; Arif , Muhammad; Suyono, Suyono; Nugraha, Mhd Nuryansah (Jurnal Media Informatika, 2024)
This research aims to create a learning model for basic locomotor jumping movements using simple games. This model was developed as a means to achieve physical education learning objectives by developing basic locomotor jumping movement skills, so that it can be used by teachers in physical education at school. The method used in this research is development research based on the method proposed by Borg and Gall, with the following research stages: (1) information collection, (2) initial draft design, (3) expert validation and revision, (4) scale small scale testing and revision, (5) large scale testing and, (6) final product, (7) effectiveness testing. Small-scale testing was carried out at SD Negeri 060875 Medan Perjuangan, large-scale testing was carried out at SD Negeri 060904 Medan Maimun. Based on the results of testing the effectiveness of the product model, the reality proves that the results of product testing in the form of a basic motor movement learning model using simple games for grade 3 elementary school students have a very good receptive level. effective. The results of the _t test are based on the results of building a basic movement learning model when jumping presented in the form of a simple game showing that the calculated t is greater than the t table. The results of the research show that in the basic jumping movement learning model there are 4 games: (a) rope jumping game (b) carpet jumping game (c) hurdle game (d) hurdle jumping game. In other words, this model of learning basic jumping movements with simple games has an influence in supporting the learning process of physical education, sports and health in grade 3 elementary school students.